2011
DOI: 10.1111/j.1365-2559.2011.04060.x
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin expression by cancer-associated fibroblasts predicts poor outcome in invasive ductal breast carcinoma

Abstract: Our results suggest that podoplanin expression by CAFs could be an unfavourable prognostic marker for IDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 36 publications
(129 reference statements)
11
95
1
Order By: Relevance
“…Moreover, expression of this marker was noted in myoepithelial cells and in stromal cancer-associated fibroblasts, what is in accordance with other authors studies [2][3][4][5][6][7][8][9][12][13][14][15][16][17]. Selected vessels were double-stained with CD34 and podoplanin.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, expression of this marker was noted in myoepithelial cells and in stromal cancer-associated fibroblasts, what is in accordance with other authors studies [2][3][4][5][6][7][8][9][12][13][14][15][16][17]. Selected vessels were double-stained with CD34 and podoplanin.…”
Section: Discussionsupporting
confidence: 76%
“…Other authors found similar relations between the above-mentioned parameter and grade, ER/PR/HER2 expression and tumour cells proliferation [16][17][18]. This result suggests the existence of a specific subpopulation of stroma cancer-associated fibroblasts with podoplanin expression that may stimulate (or may be associated with) aggressive behaviour of cancer cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The above phenomena were confirmed by studies in which the following stroma-related parameters were found to be of prognostic significance: (i) tumor-tostroma ratio (5-7); (ii) the type of tumor stroma (fibroblastdominant vs. lymphatic-dominant vs. collagen-dominant) (8-10); (iii) the presence of podoplanin-positive CAFs (ppCAFs) (11)(12)(13)(14) . Furthermore, it was suggested that CAFs might contribute to: (i) tumor initiation; (ii) proliferation, migration and invasiveness of cancer cells; (iii) tumor angiogenesis/lymphangiogenesis; (iv) tumor-induced inflammation; (v) metabolic reprogramming of the tumor microenvironment; and (vi) therapeutic resistance (4).…”
supporting
confidence: 52%
“…Ovaries (2) Epidermis basal layer Honma et al (2012); Gandarillas et al (1997) (1), (2), (3), (4), (5), (6), (7), (8) Kawase et al (2008) Squamous lung carcinoma -(2), Kitano et al (2010) Breast cancer Poor (3) Pula et al (2011) Intrahepatic cholangiocarcinoma Poor…”
Section: Acknowledgementsmentioning
confidence: 99%